ARABIC LANGUAGE LEARNING AT INSTITUTIONS FOR NON-ISLAMIC EDUCATION STUDY PROGRAMS - Mustolikh Khabibul Umam; Daluti Delimanugari; Ana Dwi Wahyuni; Ike Hilatun Nisa (STAI Asy-Syukriyyah, 2024)
The development of Arabic language skills mostly targets Muslim communities. However, there are specific obstacles to the acquisition of these language skills in higher education institutions, which largely arise from the need to accommodate students of various religious affiliations in their studies. The aim of this research is to reveal the benefits, weaknesses, prospective benefits, and potential drawbacks of incorporating Arabic into the curriculum of higher education institutions. This research uses qualitative methods and combines data from students, lecturers and policy documents related to curriculum development. Before reaching a conclusion, the data obtained is categorized, displayed and examined. Findings show that these institutions have valuable assets such as skilled Arabic lecturers and dedicated language and study facilities. However, the shortcomings of this institution stem from the lack of linguistic skills of teachers in several disciplines, namely the sharia economics study program and Islamic family law.